Uji Total Flavonoid Dan Aktivitas Antioksidan Fraksi Aktif Biji Kopi Robusta (Coffea canephora L. ) Sebagai Diabetik Ulcer - Elpina Br Perangin-Angin; Novitaria Br Sembiring; Vera Estefania Kaban (Journal of Pharmaceutical and Sciences, 2026)
Diabetes mellitus is a chronic metabolic disease frequently accompanied by serious complications, including diabetic foot ulcers, which require comprehensive management and supportive therapies derived from natural sources. Robusta coffee beans (Coffea canephora L.) contain various bioactive compounds with potential antioxidant properties that may support wound healing. This study aimed to determine the total flavonoid content and evaluate the antioxidant activity of active fractions of robusta coffee beans. An experimental laboratory design was applied, involving maceration using 96% ethanol followed by solvent fractionation with n-hexane, ethyl acetate, and water. Total flavonoid content was determined using ultraviolet–visible spectrophotometry with quercetin as the reference standard, while antioxidant activity was evaluated using the 2,2-diphenyl-1-picrylhydrazyl assay with vitamin C as a comparator. The results showed an extraction yield of 14.33%, and phytochemical screening confirmed the presence of alkaloids, flavonoids, phenolic or tannin compounds, saponins, and triterpenoids. All fractions exhibited very strong antioxidant activity, with the ethyl acetate fraction demonstrating the highest activity, comparable to vitamin C, whereas the highest total flavonoid content was observed in the n-hexane fraction. In conclusion, robusta coffee beans possess strong potential as a natural antioxidant source and may be developed as a supportive alternative therapy for diabetic wound management.